Positional fatty acids in triacylglycerols and their adiposity behaviour in C57BL/6 mice / Gouk Shiou Wah - Gouk, Shiou Wah (2014)
The main objective of present study is to establish the relationship between positional fatty acids in triacylglycerols and obesity. The inferences drawn from the in vivo studies have been used in the design of prospective structured lipids to reduce obesity risk. In the effort to evaluate the effect of positional fatty acids on obesity, an accurate and precise analytical method to analyse positional distribution of fatty acids within the glycerol moiety is an important prerequisite. An elegant, user-friendly and accurate analytical method using quantitative 13C NMR spectroscopy (qCNMR) has been fully established in the present study. A regiospecific analysis data using qCNMR was attainable within 44 minutes, much shorter relative to the conventional methods which use a combination of chromatographic techniques. Besides, the current method provides quantitative results with high accuracy by virtue of direct measurement and negligible sample preparation prior to the analysis. Occurrence of acyl migration during the course of sample pre-treatment is omitted. The applicability as well as the versatility of the present method had been accessed in various oils and fats, reaction intermediates of chemical interesterification and extracted lipids from biological samples with systematic errors were less than 2.0 mol%. As a summary, a cookbook approach for qCNMR in the regiospecific analysis of oils and fats from diverse sources has been established. Correlation between the positional fatty acids within glycerol moiety and the accretion of fat was investigated in two in vivo studies using C57BL/6 mouse model. The positional distribution of saturated fatty acid (SFA) was found to exert a more pronounced effect on body fat deposition than the total SFA content. The extent of fat deposition will be lessened in the event of long chain SFA (C16:0 and above) occur predominantly at the sn-1,3 positions of triacylglycerols. Among the different chain length of SFA, stearic acid (C18:0) was found to be more efficient in reducing fat deposition than palmitic acid (C16:0) at the similar positions. It is postulated that after the action of 1,3-specific pancreatic lipase, non-esterified SFA will suffer delayed absorption and being excreted in the faeces due to the formation of insoluble calcium soaps. Consequently, the resynthesis of triacylglycerols in chylomicron and eventually their deposition in adipose tissues will be reduced. In accordance with the findings from both in vivo studies, structured lipid which aims to alleviate the risk of obesity has been designed. An even longer SFA, namely behenic acid (C22:0), was incorporated into the sn-1,3 positions of triacylglycerols in palm olein iodine value (IV) 56 and high-oleic sunflower oil. To achieve sustainable chemistry, immobilised lipases from the strain of Rhizomucor miehei (Lipozyme RM IM, NovozymesTM) and Thermomyces lanuginosa (Lipozyme TL IM, NovozymesTM) were employed in the current synthesis work. The synthesized structured lipids which contain high amount of BOO and BOB molecular species may serve potential applications in functional dietary fats, for instance, bakery shortening, trans-fat-free margarine, vanaspati and cocoa butter equivalent, with the additional health benefit in terms of giving lower risk towards the body fat deposition.